Homo Loquens Versus Homo Ludens. Glottodidactic Reflections on Johan Huizinga’s Concept of Culture - Rudziński, Grzegorz (Ludicity in (Glotto)Didactic, 2020)
As far as teaching/learning of foreign languages belongs to the area of culture, it is a form of play as well as (according to J. Huizinga’s point of view) the politics, drama and war are. There are several parallels between a language course and a game. Most of Huizinga’s claims about the essence of play can be rewritten with the substitution: instead of the noun “a fun” we can write an expression “a learning a language” – without losing their meaningfulness. When we identify language acquisition as fun we can describe the first in terms of the second. The success in playing and learning a language is given to those who join both enthusiastically, treat both seriously, spare no effort, respect the rules, actively participate in them and play fair.